Increased Brain Iron Deposition in the Putamen in Patients with Type 2 Diabetes Mellitus Detected by Quantitative Susceptibility Mapping - Jing Li; Qihao Zhang; Nan Zhang; Lingfei Guo (Journal of Diabetes Research)
Background. The underlying brain structural changes in type 2 diabetes mellitus (T2DM) patients have attracted increasing attention. The insulin-resistant state causes iron overload in neurons and leads to lesions in the central nervous system. Quantitative susceptibility mapping (QSM) can provide a noninvasive quantitative analysis of brain iron deposition. We aimed to compare the difference of brain iron deposition in the gray matter nucleus between T2DM patients and healthy elderly individuals using QSM. Methods. Thirty-two T2DM patients and thirty-two age- and gender-matched healthy controls (HCs) were enrolled in this research. Twenty-three patients and twenty-six HCs underwent cognitive assessments. Brain QSM maps were computed from multiecho GRE data using morphology-enabled dipole inversion with automatic uniform cerebrospinal fluid zero reference algorithm (MEDI+0). ITK-SNAP was used to measure the susceptibility values reflecting the content of iron in the regions of interest (ROIs). Results. The study included thirty-two T2DM patients (20 males and 12 females; mean age of 61.09±9.99 years) and 32 HCs (14 males and 18 females; mean age of 59.09±9.77 years). These participants had no significant difference in age or gender (P>0.05). Twenty-three patients with T2DM (11 males and 12 females; mean age, 64.65±8.44 years) and twenty-six HCs (14 males and 12 females; mean age, 62.30±6.13 years) received an assessment of cognitive function. T2DM patients exhibited an obviously (t=3.237, P=0.003) lower Montreal Cognitive Assessment (MoCA) score (26.78±2.35; HCs, 28.42±0.64; normal standard ≥26) and a higher Stroop color-word test (SCWT)-C score [87(65,110); HC, 63(60,76.75), Z=−2.232, P=0.003] than HCs. The mean susceptibility values in the putamen appeared obviously higher in T2DM patients than in HCs (t=−3.994, P<0.001). The susceptibility values and cognitive assessment scores showed no obvious association (P>0.05). However, an obvious correlation was observed between the changes in the susceptibility values in the putamen and the thalamus/dentate nucleus (r=0.404, P<0.001; r=0.423, P<0.001). Conclusion. T2DM patients showed increased susceptibility values in the putamen and had declines in executive functions, but the linear association between them was not statistically significant. Changes in susceptibility values in the putamen indicated increased iron deposition and might be used as a quantitative imaging marker of central nervous system injury in T2DM patients. QSM might be able to help probe micro neuronal damage in gray matter and provide information on diabetic encephalopathy.